2019
DOI: 10.1111/1468-2230.12389
|View full text |Cite
|
Sign up to set email alerts
|

UK Abortion Law: Reform Proposals, Private Members’ Bills, Devolution and the Role of the Courts

Abstract: UK abortion law remains unsettled, and subject to on‐going controversy and reform. This article offers a comprehensive critique of all reforms implemented or proposed since 2016. It examines reforms proposed in both Houses of Parliament and contextualises them within a public law analysis, showing both that the complex parliamentary processes relating to Private Members’ Bills have frustrated reform attempts, and that these attempts have been contradictory in their aims between the two Houses. Secondly, it exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The New Zealand Parliament (2020) voted in March 2020 to decriminalise abortion after decades of campaigning. Moves towards decriminalisation are underway in Westminster, with significant developments in the parliament and the Labour Party (Labour Party, 2019;Taylor & Wilson, 2019), but the UK currently trails behind most of its former colonies in its failure to -modernise-abortion law. In late March the UK used emergency powers enacted in response to COVID-19 to allow abortion provision via telehealth (Modin, 2020).…”
mentioning
confidence: 99%
“…The New Zealand Parliament (2020) voted in March 2020 to decriminalise abortion after decades of campaigning. Moves towards decriminalisation are underway in Westminster, with significant developments in the parliament and the Labour Party (Labour Party, 2019;Taylor & Wilson, 2019), but the UK currently trails behind most of its former colonies in its failure to -modernise-abortion law. In late March the UK used emergency powers enacted in response to COVID-19 to allow abortion provision via telehealth (Modin, 2020).…”
mentioning
confidence: 99%
“…256 In seeking further liberalising reform, campaigners elsewhere in the UK will of course face the same considerable parliamentary hurdles as those who for many decades sought further restriction of abortion law: it is nearly impossible to secure controversial reform by way of private members' bills without government support and that has proved infrequently forthcoming. 257 Nonetheless, the decades' long struggle of Northern Irish campaigners has demonstrated that sustained campaigning may eventually achieve success in unforeseen ways, with hurdles that once seemed insurmountable quickly turning to dust.…”
Section: Discussionmentioning
confidence: 99%